Neuroprotective effects of 5-(4-hydroxy-3-dimethoxybenzylidene)-thiazolidinone in MPTP induced Parkinsonism model in mice. (June 2015) - Ren, Zhili; Yang, Nan; Ji, Chao; Zheng, Ji; Wang, Tao; Liu, Yanyong; Zuo, Pingping
Abstract: Parkinson's disease (PD) is a neurological disorder characterized by degeneration of nigrostriatal dopaminergic (DAergic) system. Present treatment targeting to DAergic system solely ameliorated the symptoms but failed to retard the DAergic neuron degeneration, therefore new therapeutic methods aiming at preventing or delaying the neurodegenerative process are urgently needed. In the present study, we found that 5-(4-hydroxy-3-dimethoxybenzylidene)-2-thioxo-4-thiazolidinone (RD-1), a compound derived from rhodanine, protected DAergicneurons from neurotoxicity of MPTP/MPP + . Firstly, RD-1 significantly improved the locomotor ability in the MPTP mice model, and elevated the tyrosine hydroxylase (TH) positive cell numbers in substantianigra pars compacta (SNpc) and the integrated optical density (IOD) of TH-positive nerve fibers in striatum respectively. Since mitochondrial dysfunction plays an important role in pathogenesis of PD, thereby we investigated the molecular mechanisms of RD-1 against MPTP/MPP + neurotoxicity, focusing on its effects on the mitochondrial dysfunction. Immunoblotting analysis showed that RD-1 significantly elevated the Parkin and Miro2 expression levels in acute MPTP treated mice, and improved mitochondrial membrane potential and ATP synthesis in MPP + -treated Neuro-2a cells. Moreover, RD-1attenuated impaired mitochondrial transport and vesicle release dysfunction evoked by MPP + cytotoxicity in cultured primary mesencephalic neurons. Taken together, these results indicate that improving the mitochondrial dysfunction may be a good choice to delay the neurodegenerative progression commonly associated with PD. Highlights: RD-1 improves the motor dysfunction in the Parkinsonian mice. RD-1 enhances TH-positive neurons in SNpc and nerve fiber in striatum. RD-1 elevates the expression levels of Parkin and Miro2 expression. RD-1 attenuate mitochondrial dysfunction induced by MPP + neurotoxicity in vitro. Neuroprotection of RD-1 is mediated by improving mitochondrial dysfunction.